Healthcare Worker Occupation and Immune Response to Pneumocystis jirovecii - Tipirneni, Renuka; Daly, Kieran R.; Jarlsberg, Leah G.; Koch, Judy V.; Swartzman, Alexandra; Roth, Brenna M.; Walzer, Peter D.; Huang, Laurence (Emerging infectious diseases, 2009)
The reservoir and mode of transmission of Pneumocystis jirovecii remain uncertain. We conducted a cross-sectional study of 126 San Francisco General Hospital staff in clinical (n = 103) and nonclinical (n = 23) occupations to assess whether occupational exposure was associated with immune responses to P. jirovecii. We examined antibody levels by ELISA for 3 overlapping fragments that span the P. jirovecii major surface glycoprotein (Msg): MsgA, MsgB, and MsgC1. Clinical occupation participants had higher geometric mean antibody levels to MsgC1 than did nonclinical occupation participants (21.1 vs. 8.2, p = 0.004); clinical occupation was an independent predictor of higher MsgC1 antibody levels (parameter estimate = 0.89, 95% confidence interval 0.29-1.48, p = 0.003). In contrast, occupation was not significantly associated with antibody responses to either MsgA or MsgB. Healthcare workers may have occupational exposure to P. jirovecii. Humans may be a reservoir for P. jirovecii and may transmit it from person to person.